Transformasi Ekonomi dan Sosial Budaya di Kawasan Industri Lhokseumawe - M. Husen M.R. (Jurnal Aplikasi Manajemen, 2012)
Industrial development sector in the region is believed, in addition to opening up job opportunities, availability of various facilities and infrastructure, as well as the transformation of social and cultural economics for the community. In summary it can be said that the transformation is basically a process of fundamental change in human beings, the keyword of this working papers is transpormation, development, industry and social cultute. By placing the area of the industry will also benefit the population in the region. Namely to the opening of various economic activities and also the availability of various facilities. This reaseach in industry area in lhokseumawe, Aceh.Keywords: Transformation, development, industry, social culture.